Amaranth wastewater treatment by intensified ozonation in a rotating zigzag bed. (October 2022) - Wu, Tianyang; Zhang, Hanxiao; Liu, Zhibang; Liu, Taoran; Jiang, Peng; Arowo, Moses; Shao, Lei
Abstract: This study investigated the treatment of amaranth wastewater by ozone (O3 ) in a rotating zigzag bed (RZB), in which a high gravity environment was created to intensify O3 mass transfer and enhance the degradation of amaranth. The degradation effect of amaranth was evaluated in terms of decolorization rate of the wastewater and removal rate of chemical oxygen demand under various operating conditions. Intermediate products of amaranth degradation were also investigated to elucidate the degradation mechanisms of amaranth. Results show that the degradation efficiency generally increased with increase in initial pH, rotational speed of RZB, initial O3 concentration, gas flow rate but declined with increase in both liquid flow rate and initial amaranth concentration. The decolorization rate of the wastewater reached 92.8 % within a liquid retention time of several seconds in the RZB, suggesting that RZB can significantly enhance the mass transfer rate of O3 into liquid and thus improve the degradation efficiency of amaranth.